Financial Services Authority Regulation (POJK) Relevance Based on Sharia Principles by Financial Service Business Actors (PUJK) to Consumers Protection - Saputra, Arief Dwi; Rahmatia, Alfina; Muslimah, Muslimah; Arliansyah, Arliansyah (Borneo International Journal of Islamic Studies, 2024)
The determination of the interrelated relationship regarding POJK from the PUJK can be reviewed through its role to consumers. This study uses a systematic review of the alternative literature on a theoretical basis, antecedents, measurements review, and relevance analysis results. This research data use secondary data taken from reputable journals. Furthermore, the data is processed using the Nvivo plus 12 application through a coding similarity analysis and then drawn conclusions as a reference. The results of the study illustrate that there is a relevant relationship between POJK and sharia principles by paying attention to the relationship factors of variables and outcomes from PUJK to consumers. Theoretical contributions through originality and an agenda for future research will be developed. The policy implication of this study is to maintain and improve understanding of Islamic financial literacy through POJK based on sharia principles. The limitations of this study reveal that the relevance of the relationship between PUJK and consumers affects the results at various levels of analysis.